FARMER STRATEGY TOWARDS RISKS IN CHILI AGRIBUSINESS THROUGH INFORMAL PARTNERSHIP IN MAJU DISTRICT SIRAM VILLAGE MALANG REGENCY - Kliwon Hidayat (Socio-Economics/Agribusiness Department, 2017)
The purposes of this research are to identify chili agribusiness risks in the dryland area of medium-high land and analyze farmer strategy towards chili agribusiness risks. The research is conducted in Maju District Siram Village Malang Regency. Data are collected through interview with Juragan, who is middlemen that has power in influencing local market, and 30 chili farmers who have informal partnership with Juragan. Data in this research are analyzed descriptively and critically. The research results show that chili agribusiness risks that faced by farmers are risk in production, price, finance, and institutional risk. Those risks are related each other. The risks that bring negative impact negatively are production risk due to plant diseases, market due to price volatility, and financial risk as well. Informal partnership with Juragan, intercropping cultivation technique (also called as tumpangsari), and better technology implementation are the strategies that are performed by farmers in facing chili agribusiness risks.